Electrical discharge machining of silicon carbide using brass electrode [electronic resource] - Muhammed Fadley Che Mud, 1983-; Hamidon Musa, supervisor; Khidzir Zakaria (2013)
Thesis (Sarjana) - Universiti Teknologi Malaysia, 2013